1984
DOI: 10.1021/bi00312a020
|View full text |Cite
|
Sign up to set email alerts
|

Thermotropic and dynamic characterization of interactions of acylated .alpha.-bungarotoxin with phospholipid bilayer membranes

Abstract: The interactions of palmitoyl-alpha-bungarotoxin (PBGT) with dipalmitoylphosphatidylcholine (DPPC) bilayers have been studied by using high-sensitivity differential scanning calorimetry together with steady-state and time-resolved phosphorescence and fluorescence spectroscopy. The incorporation of PBGT into large single lamellar vesicles causes a decrease in the phospholipid phase transition temperature (Tm), a broadening of the heat capacity function, and a decrease in the enthalpy change associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 33 publications
5
15
0
Order By: Relevance
“…In order to characterize indinavir–lipid interaction and a consequence on membrane fluidity, we used diphenylhexatriene (DPH), as a membrane probe. DPH, a fluorescence probe, inserted within the hydrophobic domain of the phospholipid bilayer has been used to investigate the membrane fluidity 16–20. If indinavir binds and inserts into lipid bilayer, it would affect the lipid packing detectable as changes in DPH anisotropy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to characterize indinavir–lipid interaction and a consequence on membrane fluidity, we used diphenylhexatriene (DPH), as a membrane probe. DPH, a fluorescence probe, inserted within the hydrophobic domain of the phospholipid bilayer has been used to investigate the membrane fluidity 16–20. If indinavir binds and inserts into lipid bilayer, it would affect the lipid packing detectable as changes in DPH anisotropy.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence polarization of membrane was performed with 0.1% diphenylhexatriene (DPH) as a probe 16–20. Briefly, 2 µL of DPH (2 mM stock in tetrahydrofuran) was added to 4 mL of lipid nanoparticle suspension (with or without indinavir) containing 1 mM phospholipid and the mixture was vortexed at above the phase transition temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Although it is possible to incorporate more PBGT per vesicle (up to a protein/lipid molar ratio of 4.0 X see Figure l), we wanted to avoid the potential problem of ligand (PBGT) crowding on the vesicle surface in order to allow a more straightforward interpretation of the vesicle-microsac binding data, as well as to avoid the need for preparative sucrose density gradients to fractionate aggregated PBGT from vesicle-associated PBGT. Our previous measurements of rotational correlation times of vesicle-associated PBGT and the effect of incorporated PBGT on the thermotropic behavior of the vesicle lipid (Babbitt et al, 1984) had already indicated to us that the PBGT (ligand) was still fully dispersed and rotationally mobile on the vesicle surface at protein/lipid molar ratios as high as 5.0 X Our results indicate that incubation of an aqueous suspension of acylated toxin with vesicles preformed by the detergent dialysis method yields a quantitative and stable incorporation of PBGT into the outer leaflet of the lipid vesicles at protein/lipid molar ratios 52.5 X Binding of PBGT Vesicles to Microsac Membranes Enriched with AchR. The equilibrium binding of PBGT vesicles to AchR-enriched microsac membranes was performed with the AchR sites in great excess of the amount of PBGT vesicle offered (at least 50-fold excess) so as to allow all bindingcompetent vesicles in a given population to bind without limitation due to site availability or vesicle-vesicle crowding on the microsac surface.…”
Section: Vesicle Formation and Incorporation Of Pbgt Into Lipidmentioning
confidence: 97%
“…In the present study we investigate mixed UDCA:lipid dispersions at pH 7.0 by differential scanning calorimetry (DSC), a technique widely used in studying the phase behavior of liposomal assemblies. 1,2-Dipalmitoyl- sn -glycero-3-phosphocholine (DPPC) was chosen as the lipid substrate since the thermotropic properties leading to various lipid phase bilayer structures are well established; that is, for the pure system the sequence of the lamellar crystalline (L c ), lamellar gel (L β ‘ ), rippled gel (P β ‘ ), and liquid crystalline (L α ) phases has been well characterized as functions of temperature. This report focuses specifically on the phase behavior of DPPC bilayers in the presence of UDCA and attempts to obtain quantitative data for gaining insight into the potential roles of UDCA:phospholipid assemblies in regulating membrane function. By characterizing thermodynamically these mixed UDCA:DPPC dispersions, one is able to detail the classes of molecular aggregates induced by these bile species both within different bilayer phase structures and within membrane microdomains.…”
Section: Introductionmentioning
confidence: 99%